"HEART" IDIOMS AS PART OF BODY-PART PHRASEOLOGY - Mamashoyev Umid Ulug'bek óğli (Western European Studies, 2023)
This study explores the rich tapestry of idiomatic expressions related to the "heart" as part of body-part phraseology. Idioms, rooted in cultural and linguistic traditions, often provide unique insights into the human experience. Analyzing a selection of idioms centered around the heart, this research investigates the figurative language and metaphorical representations that contribute to the nuanced understanding of emotions, relationships, and the human condition.
Keywords: Idioms; Heart; Body-part phraseology